Acoustic–gravity waves and their role in the ionospheric D region–lower thermosphere interaction - G. Jovanovic (Annales Geophysicae)
The properties of acoustic–gravity waves (AGWs) in the ionospheric D layer and their role in the D layer–lower thermosphere interaction are studied using the dispersion equation and the reflection coefficient. These analytical equations are an elegant tool for evaluating the contribution of upward-propagating acoustic and gravity waves to the dynamics of the lower thermosphere. It was found that infrasound waves with a frequency of ω>0.035 s−1, which propagate almost vertically, can reach the lower thermosphere. Also, gravity waves with a frequency of ω<0.0087 s−1, with a horizontal phase velocity in the range of 159 m s−1 < vh < 222 m s−1 and a horizontal wavelength of 115 km < λp < 161 km, are important for the lower thermosphere dynamics. These waves can cause a temperature rise in the lower thermosphere and have the potential to generate middle-scale travelling ionospheric disturbances (TIDs). The reflection coefficient for AGWs is highly temperature-dependent. During maximum solar activity, the temperature of the lower thermosphere can rise several times. This is the situation where infrasound waves become a prime candidate for the ionospheric D layer–lower thermosphere interaction since strongly reflected gravity waves remain trapped in the D layer. Knowing the temperatures of the particular atmospheric layers, we can also know the characteristics of AGWs and vice versa.